The Imperialist - Duncan, Sara Jeannette, 1861-1922 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Imperialist" by Sara Jeannette Duncan is a novel written in the early 20th century, likely during the early 1900s. The story is set in a small Canadian town called Elgin and revolves around the Murchison family, particularly focusing on Lorne Murchison and his relationships with the townspeople and his family dynamics. The narrative examines themes of colonialism, social change, and the complications of individual ambition versus societal expectations. The opening of the novel introduces us to the character of Mother Beggarlegs, a mysterious vendor at the local market who captures the attention of children and their imaginations. As the story unfolds, we are introduced to Lorne, a young boy who demonstrates an early sensitivity towards the marginalized in his community, exemplified by his interactions with Mother Beggarlegs. The atmosphere of Elgin is richly depicted, with details about its celebrations, such as the Queen's Birthday, which shape the town's social landscape. The narrative sets the stage for the unfolding tensions between personal aspirations and the collective values of the close-knit community, hinting at the complexities of Lorne$1 (Bs journey toward adulthood and social influence. (This is an automatically generated summary.)s
Release date is 2004-03-01
Produced by Gardner Buchanan, and David Widger
Keywords: Autobiographical fiction; Imperialism -- Fiction; Domestic fiction; Political fiction; Ontario -- Fiction